Lipid Metabolism and Mitochondria: Cross Talk in Cancer - Srivastava, Anubhav; Srivastava, Pransu; Mathur, Shashank; Abbas, Sabiya; Rai, Neeraj; Tiwari, Swasti; Tiwari, Meenakshi; Sharma, Lokendra (Current Drug Targets, 2022)
Metabolic reprogramming is considered a major event in cancer initiation, progression and metastasis. The metabolic signature of cancer cells includes alterations in glycolysis, mitochondrial respiration, fatty acid/lipid and amino acid metabolism. Being at a junction of various metabolic pathways, mitochondria play a key role in fueling cancer growth through regulating bioenergetics, metabolism and cell death. Increasing evidence suggests that alteration in lipid metabolism is a common feature of metastatic progression, including fatty acid synthesis as well as fatty acid oxidation. However, the interplay between lipid metabolism and mitochondria in carcinogenesis remains obscure. The present review focuses on key lipid metabolic pathways associated with mitochondrial regulation that drive cancer phenotype and metastasis. We also review potential targets of lipid metabolism and mitochondria to improve the therapeutic regime in cancer patients. This review aims to improve our current understanding of the intricate relation of lipids with mitochondria and provides insights into new therapeutic approaches.
Keywords: cardiolipin